Upaya Meningkatkan Fokus Peserta Didik Pelajaran PAI dengan Penerapan Metode Pembelajaran Aktif Model JIGSAW di Kelas VIII SMP N 1 Sungai Beremas - Ainun Syharo Lubis; Ahmad Rajali (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to improve student focus in Islamic Religious Education (PAI) learning by implementing the Jigsaw active learning method. This research was conducted in grade 8 of SMP N 1 Sungai Beremas during the 2023/2024 academic year. Using a classroom action research (CAR) approach, this research was conducted in three cycles covering planning, action, observation, and reflection. The results showed a significant increase in student focus, from 40% in the initial condition to 91.4% in the third cycle. The Jigsaw method has proven effective in increasing student engagement and concentration, as well as optimizing material understanding.